GOOD, BAD AND DARK BITCOIN: A Systematic Literature Review - Rahardja, Untung; Aini, Qurotul; Purnama Harahap, Eka; Raihan, Raihan (Aptisi Transactions On Technopreneurship (ATT), 2021)
Crypto currency investments have been in demand since the popularity of bitcoin. Crypto currency (cryptocurrency) is a currency based on cryptography or digital currency. The birth of bitcoin as one of the important foundations in the formation of the reputation of the crypto currency. Investing in crypto currencies is considered to provide more security and large profits for investors, with a cryptographic system the crypto currency is difficult to hack and fake. This cryptocurrency is also a digital key with encryption capabilities as security and validity, as well as real value that can be exchanged as an option. The most popular type of virtual currency is known as Bitcoin, and its popularity and strength continue to increase. At first glance, Bitcoin is very confusing. But here are ten facts that can be explained in simple terms, exactly what that little coin is and what happens.